Children's perspectives on their economic activity—Diversity, motivations and parental awareness. (30th March 2020) - Xolocotzin, Ulises; Jay, Tim
Abstract: This research investigates how children from an affluent city in the UK exercise agency to construct their economic worlds. A survey ( n  = 484) showed that children (ages 10 to 14 years) conduct a range of monetary and non‐monetary activities. A second study ( n  = 83) with diaries, self‐documentation, and parental questionnaires, showed that children's economic activity involves individual and social motivations, occurs in formal and informal contexts, and is often self‐regulated. Parents acknowledge children's monetary activities and neglect non‐monetary activities. The results suggest that children's agency unfolds in diverse economic activities shaped by contextual factors and interactions with peers and parents, thereby supporting a relational view of children's agency.